Age and growth of Todaropsis eblanae (Ommastrephidae) through comparison of statoliths, beaks and eye lenses - Agus, Blondine; Battaglia, Pietro; Bellodi, Andrea; Cannas, Rita; Coluccia, Elisabetta; Cuccu, Danila (Frontiers in Marine Science, 2025)
The age composition of Todaropsis eblanae from the Sardinian waters (western Mediterranean Sea) was studied for the first time through the analysis of growth increments and the comparison of three structures: statoliths, beaks and eye lenses. The analysis was performed on 270 wild specimens of both sexes at different sizes (45-200 mm of mantle length; 6.98-443 g of total weight) and maturity stages (immature, maturing and mature) caught from July to September by trawl net. Significant differences in growth and length-weight relationship were observed between sexes, due to females reach a larger size than males. All the three structures had dimensions positively correlated with the size of the animals and showed clearly readable growth increments. Low values of IAPE, CV and PA confirmed the accuracy and good reproducibility of age readings. Eye lenses showed a very high number of growth increments (106-640), and a daily deposition was excluded. In contrast, beaks and statoliths showed NI values (70-316 and 73-310, respectively) always consistent with the size and maturity of the specimens, then a daily deposition has been suggested and their value compared. Moreover, the Mann-Whitney W-test confirmed a highly significant relationship between the number of growth increments in beaks and statoliths, suggesting that the beak can be considered a valid alternative to statoliths for age estimation in T. eblanae. The absolute growth rates confirm that females grow faster than males. Both sexes showed a higher initial growth rate, which gradually decreases, with the highest values at the age of 101-151 days, before reaching sexual maturity. According to a semelparous cycle, the estimated ages for the largest mature female (310-316 days) and male (288-292 days) suggest a lifespan of less than one year. Overall, the age and growth results reported, although referred to a specific area and a short sampling, could represent useful knowledge for a correct evaluation and management of this important commercial species in the future.